PENGARUH KONSENTRASI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI SAWI (Brassica juncea L.) - Sri Yoseva; Fitri Afriani; Islan (DINAMIKA PERTANIAN, 2021)
The aim of this work is to find out effect of several Liquid Organic Fertilizers (POC) based on their concentration and to obtain the best POC on the growth and production of mustard plants during two plantings. This research was carried out at the Experimental farm of the Faculty of Agriculture, Riau University from February to April 2020. This study was conducted at then experimental method with a one-factor Completely Randomized Design (CRD) with 5 treatments and 4 repetitions, namely tofu water with a concentration of 25% (250 ml of tofu + 750 ml water), 25% banana peel concentration (250 ml banana peel + 750 ml water). 25% concentration of rice washing water (250 ml of rice washing water + 750 ml of water), 25% concentration of eggshell (250 ml of eggshell + 750 ml of water), a mixture of tofu POC (62.5 ml) + banana peel POC (62,5 ml) + POC of rice washing water (62.5 ml) + POC of eggshell (62.5 ml). Parameters observed were plant height, number of leaves, leaf area, fresh plant weight, fresh plant weight per plot. The observational data were analyzed and continued with Duncan's New Multiple Range Test (DNMRT) at a 5% level. The results showed that the treatment of several types of POC had the same effect to each other. However, presenting POC of tofu wastewater showed that fresh yield was generally superior in terms of leaf number, fresh plant weight, and plant weight per plot.